A new genus, Neoschidium (Hemiptera: Reduviidae: Emesinae), with a redescription of the type genus, Neoschidium phasma (Distant) [Ghilianella phasma Distant and Schidium phasma (Distant)], recorded for the first time from India - Mukherjee, Paramita; Ambrose, Dunston P.; Saha, G. K.; Bal, A. (Zootaxa, 2014)
A new genus, Neoschidium was erected with the type genus, Neoschidium phasma (Distant). It was earlier described under Ghilianella Spinola 1850 as G. phasma Distant and later under Schidium Bergroth 1916 as Schidium phasma (Distant) by Bergroth (1916). Because it exhibits characters not only of Ghilianella and Schidium but also intermediate specific characters that are not found in both the genera, the type genus Neoschidium phasma (Distant) is redescribed with additional taxonomic details, morphometrics, and illustrations. It is also recorded for the first time from India.